2012
DOI: 10.1108/ohi-01-2012-b0004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Post-Disaster Housing Procurement Methods in Rural Areas of Turkey

Abstract: Earthquakes strike without warning, even though they are known to recur. It is nonetheless difficult to mobilize resources to plan for them in advance, despite the high social and economic costs that can be anticipated, and despite the humanitarian obligation to provide quality and safe housing. This research examines two post-earthquake housing reconstruction projects in rural areas of Turkey, where different procurement strategies were used. A top-down strategy was adopted in Dinar after the October 1995 ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The costs of these temporary buildings are usually high, which has been considered a waste of funds owing to the relation between the great investments needed to buy them and their short lifespan [9,10] . The usage of local resources is undoubtedly a better option than the import of solutions [11,12] . If available, local materials are probably culturally and socially more appropriate, as well as more economical, since they are familiar and avoid the high costs that transportation implies.…”
Section: Shelter After the Earthquakementioning
confidence: 99%
“…The costs of these temporary buildings are usually high, which has been considered a waste of funds owing to the relation between the great investments needed to buy them and their short lifespan [9,10] . The usage of local resources is undoubtedly a better option than the import of solutions [11,12] . If available, local materials are probably culturally and socially more appropriate, as well as more economical, since they are familiar and avoid the high costs that transportation implies.…”
Section: Shelter After the Earthquakementioning
confidence: 99%
“…Fluctuations in air temperature significantly affect occupants' thermal comfort [30]. Post-disaster permanent housing has faced criticism for its uniform, one-size-fits-all design, employing similar materials and technology, often without considering local conditions [32]. Rather than the physical environmental features, user satisfaction is influenced by personal, social, and cultural issues [33].…”
Section: Thermal Satisfactionmentioning
confidence: 99%
“…Kurum Varolgunes [34] in Turkey revealed that the failure to consider climate and topography in post-disaster permanent housing design led to occupants' dissatisfaction with thermal comfort. Dikmen and Elias-Ozkan [32] highlighted complaints about damp and cold conditions in concrete permanent houses constructed after the 1970 Gediz earthquake. Miculax and Schramm [35] reported poorer housing due to improper use of technology in new roofs compared to traditional straw roofs, which proved unsuitable for local climatic conditions.…”
Section: Thermal Satisfactionmentioning
confidence: 99%
“…In most cases, such fast-installed PTHs were the only choice for disaster victims during a postdisaster transitional period, which may unfortunately last for up to several years. 4,5 However, given their temporary nature, no indoor thermal environmental control systems were usually installed, and therefore, indoor thermal environment inside PTHs may become intolerable. 6 The long-term severity in indoor thermal environment may result in physical and mental problems for PTHs' occupants, which can be particularly true for those disaster victims.…”
Section: Introductionmentioning
confidence: 99%
“…For example, after the mega‐scale 2008 Wenchuan Earthquake in China, more than 21 million victims were resettled in PTHs during a postdisaster transitional period of up to 36 months. In most cases, such fast‐installed PTHs were the only choice for disaster victims during a postdisaster transitional period, which may unfortunately last for up to several years 4,5 . However, given their temporary nature, no indoor thermal environmental control systems were usually installed, and therefore, indoor thermal environment inside PTHs may become intolerable 6 .…”
Section: Introductionmentioning
confidence: 99%